2017
DOI: 10.1155/2017/7152406
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Bleeding Is an Independent Risk Factor for Poor Prognosis in GIST Patients

Abstract: A retrospective analysis of prognosis of GIST was used to assess the prognostic effects of hemorrhage of digestive tract induced by mucosal invasion of primary gastrointestinal stromal tumors and related mechanisms. The conclusion is that GISTs with gastrointestinal hemorrhage are more likely to recur, which indicates poor prognosis. Therefore, gastrointestinal hemorrhage may be used as a significant indicator to assess the prognosis of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 20 publications
0
40
1
Order By: Relevance
“…for s-100 and CD-34, high Ki-67, prolonged prothrombin time, male gender and the presence of metastases are the only significant risk factors that have been associated with bleeding. There have been no consistent relationships reported tumor size and GI bleeding in prior reports [14,[19][20][21]. By contrast, our study showed, that the only risk factor associated with ulceration of gastric GISTs was increased mitotic rate.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…for s-100 and CD-34, high Ki-67, prolonged prothrombin time, male gender and the presence of metastases are the only significant risk factors that have been associated with bleeding. There have been no consistent relationships reported tumor size and GI bleeding in prior reports [14,[19][20][21]. By contrast, our study showed, that the only risk factor associated with ulceration of gastric GISTs was increased mitotic rate.…”
Section: Discussioncontrasting
confidence: 92%
“…The severity of the GI bleeding varies from occult bleeding and iron deficiency anemia to life-threatening bleeding and hemorrhagic shock [10][11][12][13]. GIST ulceration and GI bleeding have great impact on patient's prognosis, usually being correlated with worse prognosis [8,[14][15][16][17][18][19][20], though there is one report of better prognosis in GISTs that bleed [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if the patient has undergone radical surgery, the recurrence rate is still 40-80% [29]. Patients with uncontrollable gastrointestinal bleeding often require emergency surgery [30]. In addition to surgical treatment, treatment with imatinib mesylate, a small molecule tyrosine kinase inhibitor, signi cantly improved the prognosis of GIST [31].…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal bleeding caused by GIST is multifactorial and can be a result of altered local mucosal blood supply, cell necrosis or tumor invading and eroding the mucosal or submucosal blood vessels [14]. Liu et al reported incidence rates of 26.4% and 54.7%, with gastric bleeding vs nongastric bleeding, respectively [15]. The stomach is larger and has more resistance to extrusion by GIST making it less prone to bleed than other non-gastric lesions.…”
Section: Discussionmentioning
confidence: 99%